2016
DOI: 10.1063/1.4943082
|View full text |Cite
|
Sign up to set email alerts
|

Optimum thickness of soft magnetic phase in FePt/FeCo permanent magnet superlattices with high energy product and large magnetic anisotropy energy

Abstract: Ab initio calculations on hard/soft (FePt)m/(FeCo)n, (m = 4, 6, 8 and n = 2-2m) magnetic superlattices show that the B2 type FeCo layers become anisotropic with varying interlayer spacing and enhanced magnetic moments. The average magnetic moment in superlattices is higher than in bulk FePt, resulting in high maximum energy product for (FePt)4/(FeCo)8 which is nearly double the calculated value for bulk FePt. The calculation of the magnetic anisotropy energy shows that the optimal thickness of the soft magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In NiFe(10-30 nm)/Co(10 nm) bilayer systems, it is found that the coercivity decreases with the increase in soft layer thickness [12]. In (FePt) m /(FeCo) n magnetic systems, magnetization increases (decreases) with the increase of FeCo (FePt) layers whereas the magnetic anisotropy energy (K U ) decreases as FeCo layer is increased [13]. By varying the thickness of the NiFe layer in the Co/NiFe bilayer, a change in interface exchange coupling and uniaxial aisotropy is observed [14].…”
Section: Introductionmentioning
confidence: 99%
“…In NiFe(10-30 nm)/Co(10 nm) bilayer systems, it is found that the coercivity decreases with the increase in soft layer thickness [12]. In (FePt) m /(FeCo) n magnetic systems, magnetization increases (decreases) with the increase of FeCo (FePt) layers whereas the magnetic anisotropy energy (K U ) decreases as FeCo layer is increased [13]. By varying the thickness of the NiFe layer in the Co/NiFe bilayer, a change in interface exchange coupling and uniaxial aisotropy is observed [14].…”
Section: Introductionmentioning
confidence: 99%
“…This conversion makes it possible to deduce (BH) max = μ 0 M 2 s /4. [ 32 ] The results demonstrate a significant increase in H c , reaching 33.5 kOe for δ Co = 100 nm, with a remanence M r of 157 emu cm −3 and a maximum magnetic energy (BH) max = 7.68 MGOe, associated with a remanence ratio M r / M s = 0.69 > 0.50. These data suggest magnetic interactions between adjacent crystallites within these films.…”
Section: Resultsmentioning
confidence: 97%
“…Soft magnetic materials are those materials that are easily magnetized and also demagnetized, [1][2][3] which can be divided into three categories: soft magnetic oxide, soft magnetic alloy and soft magnetic composites (SMCs). The soft magnetic oxide is a kind of ferrimagnetic material with medium saturation magnetization (M s ) but with low eddy current.…”
Section: Introductionmentioning
confidence: 99%